Planejamento e avaliação da comunicação organizacional em universidades públicas: uma análise do caso da UFT - Ribeiro, Bianca Zanella (Universidade Federal do Tocantins, 2015)
The present research consists on an exercise theoretical and practical in which we propose a compound that we consider basic to an organizational communication at the Federal University of Tocantins (UFT): operational directives, integrated strategic planning and a permanent evaluation and measurement system of results as a Communication Politics, a multiannual Communication Plan and an Indicators Matrix. Such proposal is the result of an association of qualitative and quantitative methods related to the practices of a case study and applied research to communication and management of public policies, and is based on theoretical approaches that emphasize the strategic potential of organizational communication mainly focused on public organizations in the education sector. The analysis is based on a diagnosis that aims to capture aspects of the complexity and dynamics of the researched institution by a communication clipping made from methods like opinion poll, bibliographical studies and documentary surveys. The kernel of discussions is the role of professionals and specialized sectors in communication in organizations, and also the role of other participants involved in the organization for the success of the communication process.